The Effect of Core Stability Training on Dynamic Balance in Taekwondo Athletes - Muh Said Ramadhan; Muhammad Yusuf Faizal Putra Anas; Jurlin Jurlin; Muhammad Aldi; Muh. Risky Bahar Bahar (CV Lentera Cendekia Indonesia, 2026)
This study aimed to determine the effect of core stability training on dynamic balance in Taekwondo athletes. Dynamic balance is an important component in sports, especially in controlling movement and changes of direction which require strong postural stability. A quasi-experimental method using a one-group pre-test and post-test design was applied. The sample consisted of six Taekwondo athletes selected through purposive sampling. The instrument used to measure dynamic balance was the Stork Test. The core stability training program was implemented over several sessions, and the data were analyzed using descriptive statistics and inferential tests to determine differences between pre-test and post-test scores. The results showed a significant improvement in dynamic balance after participating in the core stability training program, indicated by a significance value of p < 0.05. Therefore, core stability training has a significant effect on improving dynamic balance in Taekwondo athletes. This program is recommended as part of regular training to support technical performance, movement efficiency, and injury prevention, while further research is suggested to use larger samples and longer training durations. Keywords: core stability training, dynamic balance, Taekwondo athletes